Perlindungan Hak Reproduksi Korban Pemerkosaan Melalui Tindakan Aborsi: Dalam Kajian Feminist Legal Theory dan Keadilan Hakiki Perempuan - Imas Syuroya, Khofifah Indah; Husnayain, Nilna (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
Abortion cases involving rape victims are a complex legal and humanitarian issue in Indonesia, particularly because regulations and social realities have not been entirely successful in protecting women's reproductive rights. Although the 2023 Criminal Code, Law No. 17 of 2023 on Health, Government Regulation No. 28 of 2024, and Minister of Health Regulation No. 2 of 2025 have provided a legal basis for abortion practices under certain conditions, in practice, abortion policies for rape victims do not yet fully reflect substantive justice. Normatively, regulations have recognized exceptions for abortion in cases of rape and medical emergencies, but various administrative barriers, social stigma, health workers' fear of criminalization, and unequal access to services make it difficult for victims to access safe and legal abortions. This study aims to analyze the position of women victims of rape in the framework of abortion law through the Feminist Legal Theory approach and the concept of Women's True Justice. The research method used is a literature study of relevant laws, fiqh literature, and journal articles. The results of the study show that laws that appear neutral remain gender biased in practice, with women being placed as moral objects rather than subjects of dignity who are entitled to bodily autonomy. Furthermore, the concept of True Justice for Women proves that abortion for rape victims can be justified as an effort to save lives (ḥifẓ al-nafs) and restore honor (ḥifẓ al-‘ird). The conclusion of this study emphasizes that substantive justice for victims can only be realized if regulatory reforms are accompanied by gender-sensitive implementation, simpler procedures, and systematic protection for victims and medical personnel. Keywords: Reproductive Rights, Abortion, Victims of Rape.